Pengaruh ZPT Auksin dan POC Photosynthetic Bacteria (PSB) Terhadap Hasil Produksi Tanaman Kangkung Darat (Ipomoea reptans P.) - Lawolo, Andi Gusman Sarta; Zulfida, Ida; Harahap, Lutfi Henderlan (JURNAL AGROPLASMA, 2025)
Ipomoea reptans P. commonly known as water spinach, is a leafy vegetable with high economic value and is widely consumed by the Indonesian population. This plant is extensively cultivated due to its short harvest cycle of approximately 25–30 days after planting, which provides farmers with the opportunity to increase land productivity. This study was conducted on agricultural land at the Universitas Pembinaan Masyarakat Indonesia (UPMI), Medan, from June to August 2025. A factorial Randomized Block Design (RBD) 4×4 with three replications was employed. The first factor was the Auxin Plant Growth Regulator (PGR) with four levels: Z0 = control, Z1 = 50 ml/L, Z2 = 100 ml/L, and Z3 = 150 ml/L. The second factor was POC PSB with four levels: P0 = control, P1 = 50 ml/L, P2 = 100 ml/L, and P3 = 150 ml/L. The results indicated that the application of Auxin PGR significantly affected the production parameters, with treatment P2 (100 ml/L) yielding a fresh weight of 58.1 grams. Furthermore, the interaction between Auxin PGR and POC PSB had a highly significant effect on the fresh weight of plants. The optimal combination was found in treatment Z3P2 (150 ml/L Auxin + 100 ml/L POC PSB), resulting in a fresh weight of 65.7 grams. In conclusion, the combined application of 150 ml/L Auxin PGR and 100 ml/L POC PSB significantly enhances the growth and yield of Ipomoea reptans and represents an environmentally friendly alternative technology to improve horticultural productivity. Keywords: ipomoea reptans, auxin plant growth regulator, POC PSB, growth, yield